2022
DOI: 10.1186/s12943-022-01510-2
|View full text |Cite
|
Sign up to set email alerts
|

m6A modification: recent advances, anticancer targeted drug discovery and beyond

Abstract: Abnormal N6-methyladenosine (m6A) modification is closely associated with the occurrence, development, progression and prognosis of cancer, and aberrant m6A regulators have been identified as novel anticancer drug targets. Both traditional medicine-related approaches and modern drug discovery platforms have been used in an attempt to develop m6A-targeted drugs. Here, we provide an update of the latest findings on m6A modification and the critical roles of m6A modification in cancer progression, and we summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 223 publications
1
146
0
Order By: Relevance
“…The profiles of lncRNAs and m6A genes were obtained from the TCGA database. According to previous studies ( 18 , 19 ), the expression matrixes of 23 m6A genes were retrieved from the TCGA database, including the expression data of writers (METTL3,METTL14, METTL16,WTAP,VIRMA,ZC3H13,RBM15,RBM15B), readers (YTHDC1,YTHDC2,YTHDF1,YTHDF2,YTHDF3,HNRNPC,FMR1,LRPPRC,HNRNPA2B1,IGFBP1,IGFBP2,IGFBP3,RBMX), and erasers (ALKBH5 and FTO). The m6A-related lncRNAs were screened by Pearson’s correlation analysis, and 464 m6A-related lncRNAs were identified based on the criteria of |Pearson R| >0.4 and p <0.001.…”
Section: Methodsmentioning
confidence: 99%
“…The profiles of lncRNAs and m6A genes were obtained from the TCGA database. According to previous studies ( 18 , 19 ), the expression matrixes of 23 m6A genes were retrieved from the TCGA database, including the expression data of writers (METTL3,METTL14, METTL16,WTAP,VIRMA,ZC3H13,RBM15,RBM15B), readers (YTHDC1,YTHDC2,YTHDF1,YTHDF2,YTHDF3,HNRNPC,FMR1,LRPPRC,HNRNPA2B1,IGFBP1,IGFBP2,IGFBP3,RBMX), and erasers (ALKBH5 and FTO). The m6A-related lncRNAs were screened by Pearson’s correlation analysis, and 464 m6A-related lncRNAs were identified based on the criteria of |Pearson R| >0.4 and p <0.001.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, SUN et al reported that Saikosaponin D (SsD) could elevate global m6A modification level via inhibiting m6A demethylase FTO, which further relieved leukemia resistance to TKIs treatment by decreasing the stability of MTHFR and BCL-2 [ 201 ]. In addition to SsD, there are some other modulators targeting m6A regulatory proteins, such as curcumin, fusaric acid, chidamide and STM2457 [ 220 ]. The finding of these modulators targeting m6A may provide novel and effective strategies for overcoming therapeutic tolerance in cancer.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Few of the currently available FTO inhibitors are limited by its poor sensitivity and/or selectivity; (2) similarly, whether m6A and its regulators can be used as potential biomarkers for diagnosis and prognosis of hematologic tumors need to be investigated thoroughly; (3) the potential interplay between m6A and ncRNAs provides a wide scope for future researches to explore more therapeutic targets; (4) traditional medicines and natural products have convincing safety validated by generations, and they are reliable sources of novel chemical structures. Moreover, AI-assisted approaches greatly improve the efficiency in screening, assessing and optimizing potential compounds [149].…”
Section: Rheinmentioning
confidence: 99%